Fighting corruption when existing corruption-control levels count : what do wealth effects tell us? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Why are some nations more effective at battling corruption than others? Are there different determinants in the fight against corruption across developing nations? How do wealth effects play-out when existing corruption-control levels matter in the corruption battle? To investigate these concerns we examine the determinants of corruption-control throughout the conditional distribution of the fight against corruption. The following broad findings are established. (1) Population growth is a(an) tool(impediment) in(to) the fight against corruption in Low(Middle) income countries. (2) Democracy increases (decreases) corruption-control in Middle(Low) income countries. As a policy implication, blanket corruption-control strategies are unlikely to succeed equally across countries with different income-levels and political wills in the fight against corruption. Thus to be effective, corruption policies should be contingent on the prevailing levels of corruption-control and income-bracket.
Keywords: C10; H10; K10; O10; O55; 330; Corruption; Democracy; Government quality; Quantile regression; Africa